Judge's Consideration in Granting Exceptions in Trademark Cases - Elman Wahyu Koesnoto; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2025)
A trademark as part of intellectual property has an important role in protecting product identity and preventing unfair business competition. In trademark cases, exceptions are often filed by defendants to dismiss lawsuits from the early stages before entering the main case. This study aims to determine the judge's considerations in granting exceptions in trademark cases in Decision Number 52/Pdt.Sus-Trademark/2020/PN Niaga Jkt.Pst, Decision Number 72/Pdt.Sus-Trademark/2020/PN.Niaga.Jkt.Pst, and Decision Number 1/Pdt.Sus-Trademark/2024/PN Niaga Jkt.Pst and what legal efforts can be taken in granting exceptions in trademark cases. This study uses a normative juridical method with a doctrinal approach and case studies of court decisions. The data used are secondary data obtained through document analysis and case studies of court decisions. The results of this study indicate that judges in granting exceptions consider several legal aspects, such as the prematurity of the lawsuit, formal defects in the power of attorney, and the ambiguity of the lawsuit (obscuur libel). The granting of this exception is in accordance with applicable legal provisions. In addition, this study also examines the legal remedies that can be taken by parties who object to the exception decision, namely through cassation and judicial review. The conclusion of this study is that the judge's considerations in granting exceptions in trademark cases focus on legal and procedural aspects. The decision that grants the exception shows that the lawsuit filed does not meet the applicable legal requirements, such as the invalidity of the power of attorney, prematurity, and ambiguity in the lawsuit. The legal remedies that can be taken by parties who are dissatisfied with the decision to grant exceptions in trademark cases are cassation and judicial review.